Characteristics and factors influencing soil organic carbon composition by vegetation type in spoil heaps - Yao, Yiwen; Dai, Quanhou; Gao, Ruxue; Yi, Xingsong; Wang, Yong; Hu, Zeyin (Frontiers in Plant Science, 2023)
The variation of organic carbon content in spoil heaps is closely related to improving soil structure, maintaining soil fertility, and regulating soil carbon cycling balance. Analyzing the soil organic carbon content and related driving factors during the natural vegetation restoration process of spoil heaps is of great significance for promoting the accumulation of soil organic carbon in the spoil heaps. Methods: we selected spoil heaps with the same number of years of restoration to research the variations in soil organic carbon components under different vegetation types (grassland: GL, shrubland: SL, secondary forest: SF) and compared the results with those on bare land (BL).Our results showed that vegetation type and soil depth significantly affect the content of soil organic carbon components. There was no difference in soil organic carbon components between SF and SL, but both were considerably superior to GL and BL (p<0.05), and the particulate organic carbon (POC) and light fraction organic carbon (LFOC) contents of SL were the highest. A significant positive linear correlation existed between SOC and active organic carbon components. Pearson's correlation and redundancy analysis showed that the available potassium (AK) and total nitrogen (TN) contents and gravel content (GC) in the BL soil significantly impacted soil organic carbon. When vegetation is present, TN, total phosphorus (TP), and Fine root biomass (FRB) significantly affect soil organic carbon.Structural equation modelling (SEM) shows that AK and soil moisture content (SMC) directly affect the organic carbon composition content of BL, When there is vegetation cover, fine root biomass (FRB) had the largest total effect in the SEM. Soil bulk density (BD) has a negative impact on soil organic carbon, especially in the presence of vegetation.Conclusions: These findings suggest that vegetation restoration can significantly increase soil organic carbon content, FRB, AK, and TN play important roles in enhancing soil organic carbon.Supplementation with nitrogen and potassium should be considered in the bare land stage, and shrubs nitrogen-fixing functions and well-developed roots are more beneficial for the accumulation of soil organic carbon.